Real Time Collision free Robot Path planning in Dynamic Space - Javan, Sobhan; Babazadeh, Hadiseh (The ... CSI International Symposium on Artificial Intelligence & Signal Processing (Online), 2024)
Moving robots are used nowadays in real life, and it is essential to make them able to create safe paths to move in different environments automatically. In this research, the PSO algorithm along with the image processing technique, were utilized to generate a path for a mobile robot in a dynamic two-dimensional environment with some obstacles. To simulate the dynamic environment, the number, size, and position of obstacles are assumed to change randomly, and the generated path is modified at each step according to the new state. Also, the position of the target is assumed to change during the path generation. Codes are written in Python to simulate the PSO algorithm and path planning procedure, and they verify how the path can be created in a dynamic space.